Hubungan Respon Imun Humoral dengan Derajat Trombositopenia pada Pasien Demam Berdarah Dengue - Fatmawati Fatmawati; Chandra Wijaya (Jurnal Ilmu Kedokteran, 2010)
The correlation between humoral immune response with the level of of thrombocytopenia on dengue hemorrhagicfever patient The aim of this study was to know the correlation between humoral immune response with the level of ofthrombocytopenia on dengue hemorrhagic fever patient. This is a cross sectional analytical study on internal inpatientsof AwalBros Pekanbaru Hospital in August-November 2008. Population was all internal inpatients of AwalBros PekanbaruHospital with working diagnosis dengue hemorrhagic fever. There were 4 pattern of anti Dengue antibody : IgG-/IgM,IgG-/IgM+, IgG+/IgM-, IgG+/IgM+. Most of patients with IgG+/IgM+ and have secondary dengue infection Thoseresult were analyzed by Friedman statistical test. There isn’t a significant correlation between the level ofthrombocytopenia and anti dengue antibody. It show that there wasn’t a direct correlation between them. It could bedue to a cross reaction between anti dengue antibody with thrombocyte (autoantibody).